Efektifitas Penerapan Strategi Genius Learning Dalam Meningkatkan Prestasi Belajar Fiqih Siswa Kelas X MA. Al-Aman Payaman Solokuro Lamongan - Muh. Layyin farihin (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: The educational concept was even more important when a person has to enter the life in society and the workplace. Due concerned should be able to apply what is learned in school to deal with problems encountered in daily life today and tomorrow. Education is a systematic process to improve the human dignity of a holistic manner, which enables students to develop optimally. Thus, education should be a strategic vehicle for efforts to develop all the potential of the individual, so that the goal of building a complete Indonesian man can be achieved. This type of research to study